Driving smart medical diagnosis through AI-powered technologies and applications - Khang, Alex (Advances in medical diagnosis, treatment, and care (AMDTC) book series, 2024)
This book explores the vast potential to deploy precise, efficient, and impactful interventions precisely when needed in a patient's care journey. In a world where patients increasingly demand more from healthcare services, and the volume of available works and medical data escalates at an unprecedented rate, artificial intelligence and correlative technologies emerge as the driving force propelling improvements across the healthcare services continuum.